A Nationwide Analysis of the Correlation Between Work Environment and Nurses’ Job Satisfaction in Saudi Arabia's Government Hospitals - Mofadi, Hallah; Almarwani, Talahi; Al Anazi, Nawal Mohammed; S.Alotaibi, Nourah Obaid; Adawi, Dalal Othman; Al Nfeeli, Fatamah Nasser A; Alsuayed, Razan Khalid; Al Tharawi, Njoud Ali; Aloufi, Ghaziel Owayli; Al Marashi, Eman Saeed; Aldalbahi, Laila Matrouk; Alenazi, Mona Mordhi; et al. (Journal of Ecohumanism, 2024)
Background: The conditions that nurses experience at work constitute an essential factor for maintaining staff satisfaction along with current employee retention rates in hospitals. Stress and burnout together with other workplace issues have intensified the worry about healthcare employee retention. The working environment strongly shapes nurse job satisfaction while also influencing their professional retention decisions. The comprehension of these underlying factors represents an essential requirement for creating methods that enhance caregiving staff stability as well as workplace conditions. Aim: The research seeks to assess different elements of workplace environment for their impact on job satisfaction among nursing staff in Saudi Arabia. This research seeks to discover critical workplace satisfaction elements that will allow developing better retention and workplace condition enhancement strategies in Saudi governmental hospitals. Methods: The work environment assessment alongside nurse satisfaction measurements focused on 375 staff members from Saudi Arabian governmental hospitals through a cross-sectional design. Participants accessed and completed a self-serving online questionnaire for data collection which included both the Practice Environment Scale of the Nursing Work Index and the Minnesota Satisfaction Questionnaire. Data researchers employed the SPSS software for their information analyses. Results: Workers in nursing positions showed positive opinions about their workplace atmosphere particularly regarding basic nursing care delivery alongside physician collegiality. Staffing levels alongside resources came under severe dissatisfaction from respondents who numbered 18% in these areas. Women and qualified personnel with higher pay rates demonstrated distinct perspectives toward their working conditions and satisfaction according to One-Way ANOVA results. The work environment in nursing turned out to be a strong predictor of job satisfaction since it explained 37.1% of variation in nurse satisfaction levels according to multiple regression tests. Conclusion: The research demonstrates that work environment conditions significantly affect nurse satisfaction within Saudi Arabian governmental hospitals. The work environment displays some strengths but nurses require higher staffing levels together with better resource availability and enhanced compensation to reach full satisfaction and minimize attrition rates.